2013
DOI: 10.1128/jcm.03052-12
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Goat-to-Human Transmission of Methicillin-Resistant Staphylococcus aureus Sequence Type 398

Abstract: Transmission of methicillin-resistant Staphylococcus aureus (MRSA) between animals and humans is widely recognized. In this study, we describe the first case of infection of a goat and suspected transmission of MRSA ST398 to a human, which resulted in colonization of animal owners by MRSA sequence type 398. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…More recently, MRSA was detected in the nasal cavity, the vagina, and from individual dairy goat milk samples in Taiwan (Chu et al, 2012) and in milk samples obtained from clinical mastitis cases in Turkey (Aras et al, 2012), but the strains were not genotyped by multilocus sequence typing. Loncaric et al (2013) isolated MRSA from the nasal cavity and reported lung infection in a goat, also suspecting a possible transmission of the same MRSA strain to farmers.…”
Section: Short Communicationmentioning
confidence: 99%
“…More recently, MRSA was detected in the nasal cavity, the vagina, and from individual dairy goat milk samples in Taiwan (Chu et al, 2012) and in milk samples obtained from clinical mastitis cases in Turkey (Aras et al, 2012), but the strains were not genotyped by multilocus sequence typing. Loncaric et al (2013) isolated MRSA from the nasal cavity and reported lung infection in a goat, also suspecting a possible transmission of the same MRSA strain to farmers.…”
Section: Short Communicationmentioning
confidence: 99%
“…Nasal swabs of clinically healthy cattle (n = 55) and sheep (n = 38, 10 from organic farms) were cultured for MRSA; selected colonies were tested for cefoxitin resistance and confirmed as S. aureus by PCR. 7,8 Eight S. aureus isolates, originating from four different cattle and three sheep, were resistant to cefoxitin. Isolates were tested for mecA and mecC, and SCCmec were typed.…”
mentioning
confidence: 99%
“…Isolates were tested for mecA and mecC, and SCCmec were typed. 5,8 All MRSA isolates were further investigated for PVL genes, spa typing, two multiple-locus, variable-number tandem repeat analysis (MLVA) and multilocus sequence typing (MLST). 8 Amplicons (including all mecC) were sequenced by LGC Genomics (Berlin, Germany).…”
mentioning
confidence: 99%
“…Nineteen genes, except seq, were detected in this study. The most prevalent gene was sei (52, 58.4%), followed by tst-1 ( (19,21.3%). The prevalence rates of 5 genes were between 10% and 20%, namely, seh (13, 14.6%), ser (12, 13.5%), ses (11, 12.4%), set (10, 11.2%)and sed (9, 10.1%).…”
Section: Profile Of Staphylococcal Se/sel/tsst-1 Genesmentioning
confidence: 99%
“…This indicated that pigs were important reservoir for human-infected MRSA. Recent studies also found that MRSA ST398 could be isolated from other animals, such as goats [19], rabbits [20], and cattle [21], etc. In addition, methicillin-susceptible S. aureus (MSSA) isolated from both human and animals also exhibited multi-drug resistance (MDR) to various classes of antimicrobials [22,23].…”
Section: Introductionmentioning
confidence: 98%